Designing a Risk Assessment Tool for Artificial Intelligence Systems - Nagbøl, Per Rådberg; Müller, Oliver; Krancher, Oliver (The Next Wave of Sociotechnical Design)

Drift Detection in Text Data with Document Embeddings - Feldhans, Robert; Wilke, Adrian; Heindorf, Stefan; Shaker, Mohammad Hossein; Hammer, Barbara; Ngonga Ngomo, Axel-Cyrille; Hüllermeier, Eyke (Intelligent Data Engineering and Automated Learning – IDEAL 2021)

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

HighPerMeshes – A Domain-Specific Language for Numerical Algorithms on Unstructured Grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz-Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Euro-Par 2020: Parallel Processing Workshops)
Solving partial differential equations on unstructured grids is a cornerstone of engineering and scientific computing. Nowadays, heterogeneous parallel platforms with CPUs, GPUs, and FPGAs enable energy-efficient and computationally demanding simulations. We developed the HighPerMeshes C++-embedded Domain-Specific Language (DSL) for bridging the abstraction gap between the mathematical and algorithmic formulation of mesh-based algorithms for PDE problems on the one hand and an increasing number of heterogeneous platforms with their different parallel programming and runtime models on the other hand. Thus, the HighPerMeshes DSL aims at higher productivity in the code development process for multiple target platforms. We introduce the concepts as well as the basic structure of the HighPerMeshes DSL, and demonstrate its usage with three examples, a Poisson and monodomain problem, respectively, solved by the continuous finite element method, and the discontinuous Galerkin method for Maxwell’s equation. The mapping of the abstract algorithmic description onto parallel hardware, including distributed memory compute clusters, is presented. Finally, the achievable performance and scalability are demonstrated for a typical example problem on a multi-core CPU cluster.
Keywords: tet_topic_hpc

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Learning Choice Functions via Pareto-Embeddings - Pfannschmidt, Karlson; Hüllermeier, Eyke (Lecture Notes in Computer Science)

Hyper-parameterized Dialectic Search for Non-linear Box-Constrained Optimization with Heterogenous Variable Types - Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)
Keywords: pc2-ressources

On the Real-World Instantiability of Admissible Hash Functions and Efficient Verifiable Random Functions - Jager, Tibor; Niehues, David (Lecture Notes in Computer Science)
Verifiable random functions (VRFs) are essentially digital signatures with additional properties, namely verifiable uniqueness and pseudorandomness, which make VRFs a useful tool, e.g., to prevent enumeration in DNSSEC Authenticated Denial of Existence and the CONIKS key management system, or in the random committee selection of the Algorand blockchain. Most standard-model VRFs rely on admissible hash functions (AHFs) to achieve security against adaptive attacks in the standard model. Known AHF constructions are based on error-correcting codes, which yield asymptotically efficient constructions. However, previous works do not clarify how the code should be instantiated concretely in the real world. The rate and the minimal distance of the selected code have significant impact on the efficiency of the resulting cryptosystem, therefore it is unclear if and how the aforementioned constructions can be used in practice. First, we explain inherent limitations of code-based AHFs. Concretely, we assume that even if we were given codes that achieve the well-known Gilbert-Varshamov or McEliece-Rodemich-Rumsey-Welch bounds, existing AHF-based constructions of verifiable random functions (VRFs) can only be instantiated quite inefficiently. Then we introduce and construct computational AHFs (cAHFs). While classical AHFs are information-theoretic, and therefore work even in presence of computationally unbounded adversaries, cAHFs provide only security against computationally bounded adversaries. However, we show that cAHFs can be instantiated significantly more efficiently. Finally, we use our cAHF to construct the currently most efficient verifiable random function with full adaptive security in the standard model.
Keywords: Admissible hash functions; Verifiable random functions; Error-correcting codes; Provable security

Modeling and Analyzing Architectural Diversity of Open Platforms - Jazayeri, Bahar; Schwichtenberg, Simon; Küster, Jochen; Zimmermann, Olaf; Engels, Gregor (Advanced Information Systems Engineering)

Using Abstract Contracts for Verifying Evolving Features and Their Interactions - Knüppel, Alexander; Krüger, Stefan; Thüm, Thomas; Bubel, Richard; Krieter, Sebastian; Bodden, Eric; Schaefer, Ina (Lecture Notes in Computer Science)
Today, software systems are rarely developed monolithically, but may be composed of numerous individually developed features. Their modularization facilitates independent development and verification. While feature-based strategies to verify features in isolation have existed for years, they cannot address interactions between features. The problem with feature interactions is that they are typically unknown and may involve any subset of the features. Contrary, a family-based verification strategy captures feature interactions, but does not scale well when features evolve frequently. To the best of our knowledge, there currently exists no approach with focus on evolving features that combines both strategies and aims at eliminating their respective drawbacks. To fill this gap, we introduce Fefalution, a feature-family-based verification approach based on abstract contracts to verify evolving features and their interactions. Fefalution builds partial proofs for each evolving feature and then reuses the resulting partial proofs in verifying feature interactions, yielding a full verification of the complete software system. Moreover, to investigate whether a combination of both strategies is fruitful, we present the first empirical study for the verification of evolving features implemented by means of feature-oriented programming and by comparing Fefalution with another five family-based approaches varying in a set of optimizations. Our results indicate that partial proofs based on abstract contracts exhibit huge reuse potential, but also come with a substantial overhead for smaller evolution scenarios.

Pool-Based Realtime Algorithm Configuration: A Preselection Bandit Approach - El Mesaoudi-Paul, Adil; Weiß, Dimitri; Bengs, Viktor; Hüllermeier, Eyke; Tierney, Kevin (Learning and Intelligent Optimization. LION 2020.)

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Schema Compliant Consistency Management via Triple Graph Grammars and Integer Linear Programming - Weidmann, Nils; Anjorin, Anthony (Proceedings of the 23rd International Conference on Fundamental Approaches to Software Engineering, FASE 2020)

Modeling and Analyzing Architectural Diversity of Open Platforms - Schwichtenberg, Bahar; Schwichtenberg, Simon; Küster, Jochen; Zimmermann, Olaf; Engels, Gregor (Advanced Information Systems Engineering)

Forward-Secure 0-RTT Goes Live: Implementation and Performance Analysis in QUIC - Dallmeier, Fynn; Drees, Jan P.; Gellert, Kai; Handirk, Tobias; Jager, Tibor; Klauke, Jonas; Nachtigall, Simon; Renzelmann, Timo; Wolf, Rudi (Cryptology and Network Security)
Modern cryptographic protocols, such as TLS 1.3 and QUIC, can send cryptographically protected data in “zero round-trip times (0-RTT)”, that is, without the need for a prior interactive handshake. Such protocols meet the demand for communication with minimal latency, but those currently deployed in practice achieve only rather weak security properties, as they may not achieve forward security for the first transmitted payload message and require additional countermeasures against replay attacks.Recently, 0-RTT protocols with full forward security and replay resilience have been proposed in the academic literature. These are based on puncturable encryption, which uses rather heavy building blocks, such as cryptographic pairings. Some constructions were claimed to have practical efficiency, but it is unclear how they compare concretely to protocols deployed in practice, and we currently do not have any benchmark results that new protocols can be compared with.We provide the first concrete performance analysis of a modern 0-RTT protocol with full forward security, by integrating the Bloom Filter Encryption scheme of Derler et al. (EUROCRYPT 2018) in the Chromium QUIC implementation and comparing it to Google’s original QUIC protocol. We find that for reasonable deployment parameters, the server CPU load increases approximately by a factor of eight and the memory consumption on the server increases significantly, but stays below 400 MB even for medium-scale deployments that handle up to 50K connections per day. The difference of the size of handshake messages is small enough that transmission time on the network is identical, and therefore not significant.We conclude that while current 0-RTT protocols with full forward security come with significant computational overhead, their use in practice is feasible, and may be used in applications where the increased CPU and memory load can be tolerated in exchange for full forward security and replay resilience on the cryptographic protocol level. Our results serve as a first benchmark that can be used to assess the efficiency of 0-RTT protocols potentially developed in the future.

Considering Context in Design Science Research: A Systematic Literature Review - zur Heiden, Philipp (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry)

Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie M.; Furman, Susanne M.; Acar, Yasemin (HCI for Cybersecurity, Privacy and Trust)

A Value-Centered Approach for Unique and Novel Software Applications - Senft, Björn; Rittmeier, Florian; Fischer, Holger Gerhard; Oberthür, Simon (Design, User Experience, and Usability. Practice and Case Studies)